The Effect of Company Size on Profitability with Capital Structure as a Moderating Variable in Islamic Banks - Bustam/Sinar, Marwah Yunita; Rismawati; Syamsuddin, Sofyan (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The study aims to analyze the impact of corporate size on profitability with capital structure as a moderation variable on sharia banks in Indonesia. The secondary data used came from the annual financial reports of Bank Syariah Indonesia (BSI) and Bank Muamalat Syariah (BMS) for the period 2020-2023. This research method uses simple linear regression analysis and Moderated Regression Analysis (MRA). The results show that the size of a company measured by the natural logarithm (LN) of the total assets has a significant influence on profitability measureed by the return on assets (ROA). These findings indicate that larger companies tend to have better financial performance and are able to attract more investment. The research has made important contributions in formulating strategies to improve financial performance and attract investment in Sharia banking companies.